2022
DOI: 10.1038/s41598-022-25831-w
|View full text |Cite
|
Sign up to set email alerts
|

Flow dynamics through discontinuous clogs of rigid particles in tapered microchannels

Abstract: Suspended particles flowing through complex porous spaces exhibit clogging mechanisms determined by factors including their size, deformability, and the geometry of the confinement. This study describes the clogging of rigid particles in a microfluidic device made up of parallel microchannels that taper from the inlet to the outlet, where the constriction width is approximately equal to the particle size. This converging geometry summarizes the dynamics of clogging in flow channels with constrictions that narr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…100−102 This threshold is dependent on various factors, such as the pore-to-colloid size ratio, colloid deformability, geometry of the confinement, environmental temperature, and pressure. 103,104 In our simulations with the specific condition…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…100−102 This threshold is dependent on various factors, such as the pore-to-colloid size ratio, colloid deformability, geometry of the confinement, environmental temperature, and pressure. 103,104 In our simulations with the specific condition…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In line with previous studies, jamming in colloidal systems is observed only when the colloid volume fraction surpasses a specific threshold, known as the jamming threshold. This threshold is dependent on various factors, such as the pore-to-colloid size ratio, colloid deformability, geometry of the confinement, environmental temperature, and pressure. , In our simulations with the specific condition ( E c–p = E c–p,3 , E c–c = E c–c,2 , d = 0.30, and Δ P = 15 ε/σ 3 ), we identify the critical threshold for jamming to be around a colloid volume fraction of 0.48. Notably, this threshold slightly lowers when Δ P is increased to 23 ε/σ 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Flow tests are typically stopped after 1500 s, or when clogs begin to grow into the inlet region connecting all channels, a phenomenon which can be observed by eye. Further, clogs do not move or dislodge during the flow tests [1].…”
Section: Methodsmentioning
confidence: 98%
“…The presence of suspended particles in these confined flow systems often results in the formation of clogs, which grow as more suspension flows through the channel 3 . Clog formation causes a decrease in suspension flowrate at constant driving pressures [4][5][6][7] . It can also increase the driving pressure required to maintain a constant flowrate 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides steric effects and surface interactions, channel geometry also significantly impacts the rate and pattern of clogging by suspended particles [31][32][33][34][35] . In pores with parallel walls, clogs grow continuously from their points of inception, leading to a linear decay of flowrate with time 4 . Although increasing the entrance angle of approach to a pore can decrease clogging rates, it does not alter the continuous nature of clog growth 32 .…”
Section: Introductionmentioning
confidence: 99%